2011
DOI: 10.1371/journal.pone.0020032
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Analysis Reveals Functional Flexibility in the Selenocysteine-Specific tRNA from Mouse

Abstract: BackgroundSelenocysteine tRNAs (tRNASec) exhibit a number of unique identity elements that are recognized specifically by proteins of the selenocysteine biosynthetic pathways and decoding machineries. Presently, these identity elements and the mechanisms by which they are interpreted by tRNASec-interacting factors are incompletely understood.Methodology/Principal FindingsWe applied rational mutagenesis to obtain well diffracting crystals of murine tRNASec. tRNASec lacking the single-stranded 3′-acceptor end (Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The i 6 A modification of mt‐tRNAs is further converted to 2‐methylthio‐ N 6 ‐isopentenyladenosine (ms 2 i 6 A) by Cdk5 regulatory subunit associated protein 1 (CDK5RAP1) (Wei et al, ). The i 6 A modification appears to promote the correct ordering of the anticodon loop, thus contributing to the codon‐anticodon interaction (Ganichkin, Anedchenko, & Wahl, ). Moreover, a structural analysis of the ms 2 i 6 A modification demonstrated that the 2‐methylthio group can directly interact with the first nucleotide of a codon, stabilizing the codon‐anticodon binding and maintaining the reading frame (Jenner, Demeshkina, Yusupova, & Yusupov, ).…”
Section: Introductionmentioning
confidence: 99%
“…The i 6 A modification of mt‐tRNAs is further converted to 2‐methylthio‐ N 6 ‐isopentenyladenosine (ms 2 i 6 A) by Cdk5 regulatory subunit associated protein 1 (CDK5RAP1) (Wei et al, ). The i 6 A modification appears to promote the correct ordering of the anticodon loop, thus contributing to the codon‐anticodon interaction (Ganichkin, Anedchenko, & Wahl, ). Moreover, a structural analysis of the ms 2 i 6 A modification demonstrated that the 2‐methylthio group can directly interact with the first nucleotide of a codon, stabilizing the codon‐anticodon binding and maintaining the reading frame (Jenner, Demeshkina, Yusupova, & Yusupov, ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the crystal structures of human tRNA Sec and the archaeal tRNA Sec •PSTK complex (10,11), and those of the human tRNA Sec •SepSecS complex (12), mouse tRNA Sec (13) and another archaeal tRNA Sec •PSTK complex have also been solved (14). These studies confirmed the ‘9 + 4’ secondary structure, and revealed the characteristic features of their tertiary cores.…”
Section: Introductionmentioning
confidence: 99%
“…Murine tRNA [Ser]Sec for activity assays was the same as that crystallized recently [18]. The [ 14 C]DMAPP (dimethylallyl pyrophosphate) reaction was performed as described in [16] with minor modifications.…”
Section: Isopentenylation Assaymentioning
confidence: 99%